2016
DOI: 10.1016/j.jaip.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Asthma Control Using a Minimally Burdensome and Proactive Smartphone Application

Abstract: BACKGROUND Integrated chronic disease treatment models that enable patient self-care and shared treatment decision making have recently been shown to improve medication adherence and outcomes. Smartphone applications (apps) are a readily available means to enable this model, although sustained user engagement remains a challenge. OBJECTIVE To assess the efficacy of improving asthma control using a proactive smartphone app without required regular inputs. METHODS We designed a minimally intrusive smartphone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 21 publications
4
72
0
Order By: Relevance
“…Another randomized controlled study published in 2016 found that overweight and obese adults who used a social support app lost on average 3 kg more than patients using a self-monitoring control app over the course of the study [59]. Evidence from other recent trials has demonstrated the ability of apps to reduce consumption of sugar-sweetened beverages in women and nutrient-poor foods in men, increase activity level and reduce fatigue following stroke, and improve respiratory parameters with a reduction in corticosteroid usage among individuals with uncontrolled asthma [60-62]. …”
Section: Discussionmentioning
confidence: 99%
“…Another randomized controlled study published in 2016 found that overweight and obese adults who used a social support app lost on average 3 kg more than patients using a self-monitoring control app over the course of the study [59]. Evidence from other recent trials has demonstrated the ability of apps to reduce consumption of sugar-sweetened beverages in women and nutrient-poor foods in men, increase activity level and reduce fatigue following stroke, and improve respiratory parameters with a reduction in corticosteroid usage among individuals with uncontrolled asthma [60-62]. …”
Section: Discussionmentioning
confidence: 99%
“…points. (11) Although it have been suggested that self-management effectiveness is reduced when assessed over long-term follow-up (24), this study showed that patients had a good compliance and asthma control has been improved in a period over one year. A possible explanation for this situation could be the fact that the patients knew they were in a study and that they had to come for re-evaluation every three months, while in the study of Kauppinen et al, the patients were assessed for a much longer period (> 10 years).…”
Section: Discussionmentioning
confidence: 57%
“…Moreover, the authors emphasized that the use of the application was associated with a statistical and clinical improvement in ACT scores. (11) Results demonstrated an increase of 3 points in the mean ACT score after only 5 weeks of application use. The patients with uncontrolled asthma (an ACT score under 20 points) benefited the most, with an mean increase of 5.7…”
Section: Discussionmentioning
confidence: 93%
“…The lack of certainty in the interventions independent sustainability is one of the leading factors responsible for this resistance [4]. Electronic health apps may hold great promise for better health tracking [5], providing education [6], changing and enforcing health behaviors [7], and monitoring treatment adherence [8], however despite these benefits, they are still not being used [9]. This can be attributed due to nine key design barriers that are outlined in Chindalo et al literature review [9] (Table 1).…”
Section: Issues With Innovationmentioning
confidence: 99%